Cable-Driven Parallel Robots : Proceedings of the Second International Conference on Cable-Driven Parallel Robots - Pott, Andreas; Bruckmann, Tobias (Mechanisms and Machine Science, 2015)
This volume presents the outcome of the second forum to cable-driven parallel robots, bringing the cable robot community together. It shows the new ideas of the active researchers developing cable-driven robots. The book presents the state of the art, including both summarizing contributions as well as latest research and future options. The book cover all topics which are essential for cable-driven robots: Classification Kinematics, Workspace and Singularity Analysis Statics and Dynamics Cable Modeling Control and Calibration Design Methodology Hardware Development Experimental Evaluation Prototypes, Application Reports and new Application concepts.